2013
DOI: 10.5815/ijitcs.2013.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Digital IIR Filter Design using Real Coded Genetic Algorithm

Abstract: Abstract-The paper develops a technique for the robust and stable design of digital infinite impulse response (IIR) filters. As the error surface of IIR filters is generally mu lti-modal, g lobal optimization techniques are required to design efficient digital IIR filter in order to avoid local minima. In this paper a real-coded genetic algorithm (RCGA ) with arith meticaverage-bound-blend crossover and wavelet mutation is applied to design the digital IIR filter. A mu lticriterion optimization is emp loyed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The results obtained from MS-7 strategy are better than the results given by Tang et al [8], Tsai et al [14], Kaur et al [22] and Singh et al [23] shown in Table IV. The coefficient of low pass digital IIR filter having order 21 designed with mutation strategy MS-7 are given in Table V.…”
Section: Design Of Iir Lp Filtercontrasting
confidence: 58%
See 1 more Smart Citation
“…The results obtained from MS-7 strategy are better than the results given by Tang et al [8], Tsai et al [14], Kaur et al [22] and Singh et al [23] shown in Table IV. The coefficient of low pass digital IIR filter having order 21 designed with mutation strategy MS-7 are given in Table V.…”
Section: Design Of Iir Lp Filtercontrasting
confidence: 58%
“…In order to overcome this problem and to find the global minima, global optimization techniques like genetic algorithm (GA) [3], differential evolution (DE) [7], particle swarm optimization (PSO) [5] artificial bee colony (ABC), predator prey optimization (PPO) etc. have been used by the researchers [4,10,11,16,19,20,22,23] to design stable digital IIR filters. In this paper, a hybrid technique with differential evolution (DE) method as a global search technique and binary successive approximation (BSA) based evolutionary search method as a local search technique is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…These are orthogonal genetic algorithm, 12 hybrid Taguchi GA, 13 hybrid genetic algorithm, 14 and real coded genetic algorithm. 15 The particle swarm optimization (PSO) has been applied successfully to the IIR filter designs. Krusienski and Jenkins 16 introduced the application of PSO technique to IIR adaptive filter structures.…”
Section: Introductionmentioning
confidence: 99%
“…Another different works based on GA are reported in the literatures. These are orthogonal genetic algorithm, hybrid Taguchi GA, hybrid genetic algorithm, and real coded genetic algorithm . The particle swarm optimization (PSO) has been applied successfully to the IIR filter designs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a set of filtered signals is obtained. In the next step the approach behind the most commonly used evolutionary search algorithm namely concept of Genetic Algorithm [19,20,21,22] is used to find out the optimum signal with lowest amount of noise by using the set of filtered signals as initial population. Considering initial population is the starting point of the Genetic Algorithm where the initial population comprises set of possible solutions to the specified problem.…”
Section: Introductionmentioning
confidence: 99%